Say again - Zokić, Mira (Array, 2012)
One of the prerequisites of a safe and efficient flight is correct and timely communication. The International Civil Aviation Organization (ICAO) strongly emphases the need for improving communication in Air Traffic control and has introduced, in the Document 9835, a set of prescribed rules governing aeronautical communication. According to a survey carried out by the NASA Aviation Safety Reporting System, incorrect or incomplete pilot/controller communication is a causal or circumstantial factor in 80% of accidents and incidents. This paper gives an outline of a language technology system that should detect deviations from the prescribed usage of radiotelephony phraseology by detecting at least 80% of the types of miscommunication related to language-based problems and problems with numbers, and in that way enable the communication between air traffic controllers and pilots to be more reliable and efficient, and contribute to the improvement of aviation safety.